2021
DOI: 10.1002/lno.11979
|View full text |Cite
|
Sign up to set email alerts
|

Pelagic tunicate grazing on marine microbes revealed by integrative approaches

Abstract: Marine microorganisms comprise a large fraction of ocean carbon and are central players in global biogeochemical cycling. Significant gaps remain, however, in our understanding of processes that determine the fate, distribution, and community structure of microbial communities. Protists and viruses are accepted as being part of the microbial loop and a source of microbial mortality. However, pelagic tunicates (salps, doliolods, pyrosomes, and appendicularians), which are abundant in oceanic and coastal environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 157 publications
(203 reference statements)
1
20
0
Order By: Relevance
“…Changes in the abundance of larger, soft bodied organisms such as gelatinous zooplankters may alter the available carbon within coastal food web and redirect secondary production through the microbial loop rather than transferring energy to higher trophic levels. Additionally, filter feeding gelatinous zooplankton such as doliolids and salps can process and filter greater volumes of water at increased body sizes 44 , 45 , potentially increasing their ecological success leading to positive feedback of recovering energy from the microbial loop 46 and enhancing vertical carbon flux 47 . Kurtay et al 20 reported an increase in pico- and nanoplankton, prey items that falls within the filtering size of both doliolids and salps 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the abundance of larger, soft bodied organisms such as gelatinous zooplankters may alter the available carbon within coastal food web and redirect secondary production through the microbial loop rather than transferring energy to higher trophic levels. Additionally, filter feeding gelatinous zooplankton such as doliolids and salps can process and filter greater volumes of water at increased body sizes 44 , 45 , potentially increasing their ecological success leading to positive feedback of recovering energy from the microbial loop 46 and enhancing vertical carbon flux 47 . Kurtay et al 20 reported an increase in pico- and nanoplankton, prey items that falls within the filtering size of both doliolids and salps 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Tunicates are a fascinating group of animals with considerable diversity in size, feeding strategy, reproduction, and other fundamental life traits. However, biological studies have been more sustained on sessile tunicates (represented by solitary and colonial ascidians) than on pelagic tunicates, even though the latter are increasingly recognized as key components of the oceanic ecosystems 39 . Some pelagic tunicates are difficult to access and as a matter of fact, the abundant and ubiquitous O. dioica rapidly became one the few species to be established in a continuous laboratory culture 6 .…”
Section: Discussionmentioning
confidence: 99%
“…2e) become more important. Heterotrophic flagellates and ciliates 14,17 , and the much-larger larvaceans and salps 30,32,33 , feed on smaller phytoplankton unavailable to copepods and euphausiids 29 (Fig. 2a,c).…”
Section: Main Textmentioning
confidence: 99%
“…The ability of low-trophic position filter-feeders 17 to ingest picophytoplankton and bacteria could short-circuit the microbial loop, transferring carbon to larger sizes. However, traditional sampling techniques underestimate their role and almost no food-web models include filterfeeders 33,34,38 . Our findings highlight the unique, yet critical and overlooked role of filter-feeding zooplankton.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation